Four new cryptic Ptychadena species from the Upper Guinean rainforests of West Africa (Amphibia, Anura, Ptychadenidae) - Rödel, Mark-Oliver; Schmitz, Andreas; Penner, Johannes; Griesbaum, Frederic; Leaché, Adam D.; Ofori-Boateng, Caleb; Portik, Daniel; Doumbia, Joseph; Kouamé, N’goran G.; Kpan, T. Flora; Gonwouo, Nono L.; Nopper, Joachim; et al. (Zootaxa, 2026)
We describe four new cryptic Ptychadena species from rainforest habitats in the Guinean Forests of West Africa, a renowned biodiversity hotspot. The new taxa are diagnosed based on morphological and molecular data (the mitochondrial markers 12S and 16S, and the nuclear gene RAG1), including museomic data from the types of the morphologically most similar taxon, P. aequiplicata, which was believed to range from West Africa into western Central Africa. The four new species form a clade that is sister to a clade of Ptychadena species from East, West and Central Africa that contains the type specimens of P. aequiplicata. We consequently restrict the distribution of P. aequiplicata to records from western Central Africa. The similar morphology and colour pattern of P. aequiplicata and the four new species are most likely a convergent adaptation to their habitat, leaf litter of rainforests. All four new species depend on primary forests and seem to tolerate little to no forest alteration. This habitat preference and very small ‘Areas of Occupancy’ qualify all four new species as Endangered, according to IUCN Red List criteria. The new West African Ptychadena species comprise two clades with two species each, both including an eastern and a western species that may differ in their preference of different forest environments. The four new species thus seem to be a very promising model system to investigate the forest history of West Africa. At least in parts, they have a reproductive strategy adapted to unpredictable rainfall and high air humidity, which is distinctly different from the rest of the genus. The new species confirm the assumption that West Africa is home to a unique amphibian fauna that is markedly distinct from the rest of the continent.